Identifying lower limb specific and generalised joint hypermobility in adults: validation of the Lower Limb Assessment Score - Meyer, Kaitlin J. (BMC Musculoskelet Disord, 2017)
BACKGROUND: The Lower Limb Assessment Score (LLAS) has only been validated in a paediatric population. The aim of this study was to validate the use of the LLAS in an adult population by: i) evaluating its ability to discriminate between different extents of lower limb hypermobility, ii) establishing a cut-off score to identify lower limb hypermobility, and iii) determining if the LLAS is able to identify Generalised Joint Hypermobility (GJH). METHODS: Participants were recruited across three groups representing varying degrees of hypermobility. They were assessed using the LLAS, Beighton score and clinical opinion. Pearson’s correlation coefficient and MANOVA were used to assess between-group differences in the LLAS. The cut-off score was determined using median and inter-quartile ranges and the Receiver Operator Characteristic Curve. The ability of the LLAS to identify GJH was assessed using percent agreement with clinical opinion. RESULTS: One hundred twelve participants aged 18–40 years were recruited. The LLAS distinguished the control from the likely hypermobile and known hypermobile cohorts (both p < 0.001), as well as the likely hypermobile from the known hypermobile cohort (p = 0.003). The LLAS cut-off score for identifying lower limb hypermobility was ≥7/12 with a specificity of 86% and sensitivity of 68%. The LLAS accurately identified those with GJH with high percentage agreement compared to clinical opinion across all cohorts (69–98%). CONCLUSIONS: The LLAS is a valid tool for identifying lower limb specific hypermobility and GJH in adults at a cut-off score of ≥7/12. It demonstrates excellent specificity and moderate sensitivity, and discriminates well between extents of hypermobility. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12891-017-1875-8) contains supplementary material, which is available to authorized users.